Implementasi Akad Murabahah di Koperasi Jasa Keuangan Syariah BMT Mandiri Sejahtera Jawa Timur - Akhmad Sirojudin Munir (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2022)
In connection with the growing number of Islamic financial institutions in the country, the development of these Islamic institutions is something to be grateful for but also to be wary of. This vigilance is related to the existence of a pure sharia system that is applied or is it just a deviation from sharia principles that only participate in pinning the name”sharia” solely in order to follow the trend of market needs without paying attention to and apllying the actual sharia rules. Therefore, so that the public, especially customers, can distinguish which financial institutions are implementing financing that is in accprdance with actual Islamic law and which ones are only embedding the name of sharia. The form of murabahah financing is stil the dominantr form of financing ins Islamic banking. Murabahah is a sale and purchase contract of goods by stating the acquisition price and profit (margin) agreed between the seller and the buyer. Because the definition calls for an “ agreedprofit”, the characteristic of murabahah is that the seller must notify the buyer of purchase price of the goods and state the amount of profit added to the cost.